1996
DOI: 10.1080/00224545.1996.9714012
|View full text |Cite
|
Sign up to set email alerts
|

Conservative Orientation as a Determinant of Hopelessness

Abstract: Conservative orientation is identified with reference to authoritarianism, work ethic belief, just world belief, and endorsement of individualistic causes of social problems. This over-arching orientation is hypothesized to affect hopelessness and to be affected by self-esteem with reference to ego development theory and learned helplessness theory. Causal modeling of data obtained from 1st-year college students (N = 556) in Hong Kong supports the hypotheses, showing that a student's hopelessness relates to hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 50 publications
1
5
1
2
Order By: Relevance
“…Although the demobilizing influence of these beliefs is clear, their effect on the individual strategy of leaving the group are less clear and certain. Adherence to just‐world beliefs can provoke a sentiment of fatalism and helplessness in the face of negative outcomes (Chuen & Knowk, 1996). We would expect that people who adhere to just‐world beliefs would accept situations that are negative to ingroup interests without engaging in any individual or collective coping strategy.…”
Section: Introductionsupporting
confidence: 54%
“…Although the demobilizing influence of these beliefs is clear, their effect on the individual strategy of leaving the group are less clear and certain. Adherence to just‐world beliefs can provoke a sentiment of fatalism and helplessness in the face of negative outcomes (Chuen & Knowk, 1996). We would expect that people who adhere to just‐world beliefs would accept situations that are negative to ingroup interests without engaging in any individual or collective coping strategy.…”
Section: Introductionsupporting
confidence: 54%
“…It has been demonstrated that political ideology, which is generally linked to penal punitivity Hamilton, 1976), is frequently related to BJW (Cheung & Kwok, 1996;Dalbert, 1992;Dittmar & Dickinson, 1993;Furnham & Gunter, 1984;Smith & Green, 1984;Wagstaff, 1983;Wagstaff & Quirk, 1983). This variable was therefore included in the questionnaire design in order to test that correlations between BJW-O and penal punitivity are not influenced by political ideology.…”
Section: Study 5: Bjw and Penal Punitivitymentioning
confidence: 99%
“…Total scores range from 10 to 40 with higher scores indicating stronger selfesteem. Construct validity of the RSES was demonstrated by significant correlations with hopelessness and psychological well-being in different populations (Cheung & Kwok, 1996;Shek, 1997). The reliability between the English and Chinese language versions of RSES as estimated by intraclass correlation coefficient is .90.…”
Section: Methodsmentioning
confidence: 98%